(3GdJOQjH Ydi LhOI GdNOeI (B/s - (3jfhHGj, Jhfjs; (3ThjcGQ, Rcjs ((3GdbGgQI(B: s (3eLehYI Gdfjd GdYQHjI(B, s, 2003)
(3aj gPG GdcJGH (B: "(3GdJOQjH Ydi LhOI GdNOeI(B" (3Mhd Md GdeTcdGJ GdNOejI ddYejd NGQLjG aj GdShb, hOGNdjG aj fWGb GdeTQhY, hgh ehLg Edi JMbjb GdJhbYGJ GdOGFeI ddYedGA(B.. (3hjbOe cJGH (B\"(3Jhfj fjhHGj(B\" (3GdJOQjH Ydi LhOI GdNOeI(B\" (3OdjdG eaUdG dJUeje hJbOje HQGeL GdTQcI hGSYI GdfWGb hGdJj JgOa EdJi JMbjb JZjjQGJ jecf bjGSgG dJWhjQ LhOI GdNOeI GdJj jJe JbOjegG ddYejd(B..(3hjVe gPG GdcJGH JeQjfGJ hCacGQ hbhGFe eQGLYI eUeeI deSGYOI GdbGQF Ydi QHW eMJhi GdcJGH HXQhag GdNGUI(B. (3YfGUQ GdYed ef CLd GdLhOI Ndb GdefGN Ndb GdHfjGf GdGSGSj JbhjI SdSI GdYejd GdOGNdj aQb GdYed ef CLd GdLhOI egGQGJ LhOI GdNOeIs
Keywords: (3GdJOQjH GdGOGQjs; (3VHW GdLhOIs